PENGARUH PROMOSI, KUALITAS PRODUK DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN PADA APLIKASI TIKTOK - Adinda Aisyah; Devina Amelia Putri, Devi Purnilasari, Jeklyn Syafa Illiyin, Maya Afriyanti, Dian Sudiantini (Jurnal Ekonomi dan Bisnis, 2024)
This research aims to determine the influence of promotions, product quality and price on purchasing decisions on the TikTok application. The research method used to analyze this influence uses qualitative research, A descriptive qualitative approach allows researchers to describe in detail the phenomenon under investigation, including an understanding of key concepts, historical developments, and current trends in risk management. With social media, Tiktok can help advance promotional media or platforms as business fields or promotional media. This research concludes that the quality of the Tiktok application media as a means of distribution and application has good adaptation results if it is significantly related to media materials for trading. So this Tiktok application is very influential among the public and even influencers.